Golgi-Mediated Synthesis and Secretion of Matrix Polysaccharides of the Primary Cell Wall of Higher Plants - Driouich, Azeddine; follet-gueye, marie-laure; Bernard, sophie; kousar, sumaira; Chevalier, Laurence; Vicré, Maité; Lerouxel, Olivier (Frontiers in Plant Science, 2012)
The Golgi apparatus of eukaryotic cells is known for its central role in the processing, sorting and transport of proteins to intra- and extracellular compartments. In plants, it has the additional task of assembling and exporting the non-cellulosic polysaccharides of the cell wall matrix including pectin and hemicelluloses, which are important for plant development and protection. In this review, we focus on the biosynthesis of complex polysaccharides of the primary cell wall. We present and discuss the compartmental organization of the Golgi stacks with regards to complex polysaccharides assembly and secretion using immuno-electron microscopy and specific antibodies recognizing various sugar epitopes. We also discuss the significance of the recently identified Golgi-localized glycosyltransferases that are responsible for the biosynthesis of complex polysaccharides of the primary cell wall matrix.